1983
DOI: 10.1017/s0003581500066518
|View full text |Cite
|
Sign up to set email alerts
|

Excavations at Bigberry, near Canterbury 1978–80

Abstract: SummaryExcavations at the Iron Age hillfort of Bigberry, Kent, in 1978–80 had the object of a fresh appraisal since the excavations of 1933–4 of a site customarily regarded as the first obstacle encountered by Caesar after his second landing in Britain in 54 B.C. The main defences and those of the annexe were sectioned, and a hitherto unrecorded cross-dyke also. Various magnetic anomalies located by a geophysical survey were investigated and gave evidence of internal occupation and structures. It is suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…1). Recent excavations at this site (the only known hillfort in east Kent) have shown that occupation here probably began during the middle Iron Age, c. 350 BC but the defences do not seem to have been constructed until the 2nd century BC (Thompson 1983;Blockley & Blockley 1989). The site appears to have been abandoned around 50 BC, perhaps as a direct resul it being stormed by Caesar's troops in 54 BC (ih 246) and it was seemingly replaced by a r settlement adjacent to the River Stour, on the site modern Canterbury, some 3 km further to the < ( Fig.…”
Section: Discussionmentioning
confidence: 93%
“…1). Recent excavations at this site (the only known hillfort in east Kent) have shown that occupation here probably began during the middle Iron Age, c. 350 BC but the defences do not seem to have been constructed until the 2nd century BC (Thompson 1983;Blockley & Blockley 1989). The site appears to have been abandoned around 50 BC, perhaps as a direct resul it being stormed by Caesar's troops in 54 BC (ih 246) and it was seemingly replaced by a r settlement adjacent to the River Stour, on the site modern Canterbury, some 3 km further to the < ( Fig.…”
Section: Discussionmentioning
confidence: 93%
“…40 Dr Sheridan Bowman, F.S.A., has kindly provided two new and two revised dates for charcoal samples submitted to the Laboratory from the excavations at two Iron Age hillforts in Kent, Bigberry and Oldbury, during 1978-80 and 1983-4 respectively. 41 In addition, she has calibrated these four dates and a fifth, from Bigberry, which was measured before 1980, using the definitive curves of Stuiver and Pearson; 42 and, the two Bigberry dates, which were from the same feature we have statistically combined. Although the British Museum will be publishing all revised dates separately, it seems desirable to present the new results here, in so far as they may affect the hypotheses advanced for the chronology of these and other hillforts in south-east England.…”
Section: Bigberry and Oldbury Kentmentioning
confidence: 99%
“… 8 Champion 2007, 119. For Bigbury, see Blockley and Blockley 1989; Jessup and Cook 1936; Thompson 1983.…”
mentioning
confidence: 99%
“… 10 For deposition of serviceable metalwork as possible ritual deposits at the time of the abandonment of Bigbury, see Ashbee 2005, 160; pace Thompson 1983 who republished the metalwork and discounted ‘ritual explanations’ of the material remains, preferring to see them as abandoned possessions of the inhabitants.…”
mentioning
confidence: 99%